118. Nasopharyngeal (NP) Bacterial Detection in Infants With Respiratory Syncytial Virus (RSV) Infection: Impact on Clinical Outcomes. (26th November 2018) - Diaz, Alejandro; Bunsow, Eleonora; Garcia-Maurino, Cristina; Naples, Jeffrey; Juergensen, Alexis; Mertz, Sara; Wang, Huanyu; Salamon, Douglas; Leber, Amy; Ramilo, Octavio; Mejias, Asuncion
Abstract: Background: Previous studies suggest that RSV increases NP bacterial colonization and may facilitate infection. However, the role of NP colonization with potentially pathogenic bacteria (PPB) in the pathogenesis of RSV bronchiolitis is not well understood. We sought to determine the frequency, type, and density of NP PPB detection in infants with RSV infection compared with healthy controls (HC), and its association with clinical outcomes. Methods: Single-center, prospective study of previously healthy infants with RSV infection and age-matched HC. Inpatients (IP) were enrolled within 24 hours of hospitalization, outpatients (OP) at the ED or primary clinics and HC at well-child visits. RSV infection and the following PPB: [ S. pneumoniae, M. catarrhalis, H. influenzae, and S. aureus ] were detected and quantified by PCR. We compared demographic, clinical characteristics, and outcomes of care according to NP PPB detection. Results: From 2010 to 2018, we enrolled 815 infants: 664 with RSV infection [IP, 560; OP, 104] and 151 HC. RSV+ OP (6.1 [3.7–10.7] months) and HC (6.9 [3.8–10.8] months) were older than IP (2.5 [1.4–5.4] months; P < 0.001). Identification of ≥1 PPB was 89% in RSV+ infants [IP, 88%; OP, 90%] versus 63% of HC ( P < 0.0001). While H. influenzae or >1 PPB detection was higher in RSV infection ( P < 0.001), S. aureus detection predominated in HC ( P < 0.05; Figure 1). Frequency of S. pneumoniae detection was comparable between groups; however, S. pneumoniae loads were one log higher in RSV+ infants versus HC ( P = 0.001) adjusted for antibiotic use. Differences in colonization rates remained different in RSV+ infants versus HC across age ranges (<3, 3–6, >6–12, and >12–24 months; Figure 2). Last, RSV patients (both IP and OP) with S. pneumoniae or H. influenzae detection had fever more frequently (70%–74% vs. 25%–47%; P < 0.0001), higher clinical disease severity scores ( P = 0.01), and higher blood neutrophil counts (34%–36% vs. 16%–19%; P < 0.001), versus those with M. catarrhalis, S. aureus detection or PCR negative. In addition, NP detection of H. influenzae in RSV children was associated with higher frequency of atelectasis/consolidation by chest X-ray ( P < 0.005). Conclusion: These data suggest that NP colonization with PPB is high in infants with RSV infection independent of age, and that specific bacteria, namely S. pneumoniae and H. influenzae, are associated with enhanced clinical disease severity. Disclosures: A. Leber, Nationwide Children's Hospital: Research Contractor, Research support. O. Ramilo, Janssen Scientific Affairs, LLC: Consultant, Consulting fee. A. Mejias, Janssen: Grant Investigator and Scientific Advisor, Consulting fee and Research grant. Abbvie: CME talks, Speaker honorarium.